OBVIOUSNESS OF EXCLUSION? IMAGES OF ROMA IN CONTEMPORARY CZECH LITERATURE - Gawarecka, Anna (Porównania, 2018)
Martin Šmaus, Zdeněk Šmíd and Zdeněk Zapletal are contemporary Czech writers whose literary works comment the situation of the social, national and ethnic minorities in nowadays Czech society. The discrimination of Roma becomes the topic of presentation in the novels of these writers. On the other hand, it functions as a starting point for the discussion about the sense of the collective exclusion in general. All authors try to express someone else’s point of view which means that they make use of the narrative signs of empathy.